Alluaudite Battery Cathodes. Issue 7 (16th April 2020) - Dwibedi, Debasmita; Barpanda, Prabeer; Yamada, Atsuo
Abstract: Rechargeable batteries have emerged as ubiquitous and indispensable technologies of the 21st century, propelling myriads of consumer electronics and ushering a new era of electric vehicles and stationary grid storage. Since the commercialization of Li‐ion batteries by SONY (approximately in the year 1991), the secondary battery sector has seen unprecedented growth with diverse applications touching global populations across socioeconomic strata. There is a steady quest to develop a wide range of batteries to cater diverse global demands from milliwatt‐scale electronics to megawatt‐scale grid‐storage applications. In this journey, Li‐ion batteries are complemented by various post‐Li‐ion chemistry (e.g., Na +, K +, Mg 2+, Ca 2+, and Al 3+ ‐ion batteries), conversion mechanism‐based systems (e.g., Li–S, Na–S, and Li–O2 ) as well as renewed development of pre‐Li‐ion era technologies like aqueous batteries. Cathodes sit at the core with command over the net cost and performance of batteries. Various polyanionic cathodes have been developed to date, often guided by structure of naturally occurring minerals. One such mineral system is alluaudite, named after French geologist François Alluaud. The current article portrays the discovery and development of the alluaudite class of polyanionic cathode materials for rechargeable batteries. The structure and electrochemical properties of various alluaudite insertion materials are gauged along with possible future perspectives. Abstract : Alluaudite minerals, with their open structure and wide chemical compositions, offer a fertile chemical playground for material chemists to unveil a new polyanionic class of insertion materials with appealing electrochemical attributes for Li‐ion and Na‐ion batteries. This article presents an overview of the alluaudite class of battery electrodes, discussing the recent findings and future perspectives.